Analisis Teknik Slap Bass Elektrik Alain Caron pada Karya Intrumental D-code - Christoffel, Yuda Willem (Program Studi Pendidikan Musik, 2022)
Analysis of Electric Bass Slap Technique Alain Caron on Intrumental D-code. Thesis. Jakarta: Music Education Study Program, Faculty of Languages ​​and Arts, Jakarta State University 2021. The purpose of this study was to analyze and describe the electric slap bass technique used in the instrumental D-code work. This research method uses qualitative methods with a descriptive approach. The research was conducted in September 2020 - January 2021, at Taman Harapan RT 014 RW 003 Cawang, East Jakarta. Data collection was carried out by means of observation, literature study, interviews and documentation. For data analysis using data reduction, data presentation, and conclusion (verification). The data validity technique used triangulation. The result of this research, this instrumental D-code work has the form A-B-A-C-A-D-C'-D'-C'- A. Time signature 4/4, approximate tempo: 115, with a D minor scale. The total number of bars in this work is 106 bars. In general, the techniques found in D-code instrumental work are innovative slap techniques. This study divides these techniques into right hand and left hand techniques. Included in the right hand technique are the double thumb technique and the double pluck technique (pluck 1, pluck 2). Whereas the use of left hand techniques includes hammer-on, pull-off, barre, barring chord, slide, string skipping.